2017
DOI: 10.1049/mnl.2017.0015
|View full text |Cite
|
Sign up to set email alerts
|

Wettability evolution of different nanostructured cobalt films based on electrodeposition

Abstract: The wettability evolution of eight different types of nanostructured cobalt films is investigated using galvanostatic electrodeposition. The morphology, which evolves from a plump, pea‐like structure to cone, pyramid, shell, fluffy cone, fluffy shell and flower structures can be controlled by changing the anion type in the electrolyte or the deposition current density. A growth mechanism is proposed based on cathodic anomalous absorption theory, which explains both the influence of the anion type on the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Various biomimetic studies found that multi-scaled microstructures can enhance the hydrophobicity of natural surfaces, with a typical example of a lotus leaf [ 73 , 90 , 91 , 92 , 93 , 94 , 95 ]. It mainly includes two ways: 1. the droplet infiltrates the nanostructures, 2. multi-scaled microstructure provides more pinning points during the depinning stage.…”
Section: Corrections In the Wetting Transition Mechanism On Heterogen...mentioning
confidence: 99%
“…Various biomimetic studies found that multi-scaled microstructures can enhance the hydrophobicity of natural surfaces, with a typical example of a lotus leaf [ 73 , 90 , 91 , 92 , 93 , 94 , 95 ]. It mainly includes two ways: 1. the droplet infiltrates the nanostructures, 2. multi-scaled microstructure provides more pinning points during the depinning stage.…”
Section: Corrections In the Wetting Transition Mechanism On Heterogen...mentioning
confidence: 99%
“…Great achievements have been made in both theoretical research and practical construction. The scope of research has also expanded from the initial self-cleaning functional areas [6] to anti-fog [7], resistance reduction [8,9], corrosion prevention [10][11][12], anti-frozen [13], anti-adhesion [14,15] and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring surfaces vary widely in wettability, depending on their geometrical structure and chemical composition. In recent years, a number of techniques for preparing superhydrophobic surfaces have been developed, such as chemical etching [10, 11], electrodeposition [12, 13], flow plating [14], solution immersion [15], interference lithography [16] and High Speed‐Wire Cut Electrical Discharge Machining (HS‐WEDM) processing [17]. However, most of these methods are limited by their technical complexity and the need for expensive equipment, which greatly increase the final production costs.…”
Section: Introductionmentioning
confidence: 99%